Is well-being prior to receiving rehabilitation services associated with postrehabilitation mental health and functioning?. (1st February 2021) - Simning, Adam; Caprio, Thomas V.; Infurna, Frank J.; Seplaki, Christopher L.
Abstract: Objectives: Millions of older adults receive rehabilitation services every year, which aim to restore, maintain, or limit decline in functioning. We examine whether lower reported well-being prior to receiving rehabilitation services is associated with increased odds of worsening anxiety symptoms, depressive symptoms, and impairment in self-care and household activities following rehabilitation. Methods: Data come from the National Health and Aging Trends Study (NHATS), an annual survey of a nationally representative sample of Medicare beneficiaries aged 65 years and older. Our sample consists of 811 NHATS participants who, in the 2015 interview, had information on well-being and, in the 2016 interview, reported receiving rehabilitation services in the prior year. Results: In multivariable logistic regression analyses, compared to the highest quartile, those in the lowest quartile of well-being at baseline have increased odds of having worsening depressive symptoms (OR = 9.25, 95% CI: 3.78–22.63) and worsening impairments in self-care activities (OR = 2.39, 95% CI: 1.12–5.11). Conclusion: Our findings suggest that older adults with the lowest levels of baseline well-being may be susceptible to having worsening depressive symptoms and impairment in self-care activities following rehabilitation services. Examination on whether consideration of well-being during the rehabilitation process could lead to better mental health and functional outcomes following rehabilitation is needed.